Care Plan for Community-Acquired Pneumonia - Thomas Marrie; The Community-Acquired Pneumonia Outpatient Intravenous Antibiotic Therapy Working Group (Canadian Journal of Infectious Diseases)
This paper presents a critical pathway for the treatment of pneumonia that has been shown to be effective in a randomized clinical trial. The pathway uses a pneumonia-specific severity of illness score to guide the admission decision. Early administration of antibiotics (within 8 h of arrival at the emergency room) is stressed.